(untitled) (Proceedings of the International Conference on Public Health, 2017)
Breast cancer is the most frequently diagnosed malignant disease among women in the United Arab Emirates (UAE), and the incidence rate is rising. Breast cancer early detection practices through regular screening have been found to reduce morbidity and mortality from this disease. This study aims to explore the knowledge, beliefs, attitudes, and practices towards breast cancer and its screening methods among women living in the emirate of Ras Al Khaimah (RAK). One hundred and two women who met the study’s inclusion criteria were interviewed. Pearson’s chi-squared test and multivariate logistic regression analysis were performed in the statistical analysis. Relatively low participation rates in breast cancer screening practices (BCSP) were found. Women who stated that their doctors talked to them about breast cancer were significantly more likely to undergo BCSP (p <0.05). Fear of being diagnosed with breast cancer, lack of a doctor’s recommendation and perceived discomfort with breast screening were strongly associated with not planning to practice clinical breast examination (CBE) or mammography screening in the following 12 months. The study findings indicated that RAK women’s knowledge and practice of breast cancer early detection screenings are currently inadequate. Establishing a culturally acceptable health education program with appropriate interventions is required.